Direct production of furfural in one-pot fashion from raw biomass using bronsted acidic ionic liquids - Matsagar, Babasaheb M.; Hossain, Shahriar A.; Islam, Tofazzal; Alamri, Hatem R.; Alothman, Zeid A.; Yamauchi, Yusuke; Dhepe, Paresh L.; Wu, Kevin C. W. (Scientific Reports, 2017)
The conversion of raw biomass into C5-sugars and furfural was demonstrated with the one-pot method using Bronsted acidic ionic liquids (BAILs) without any mineral acids or metal halides. Various BAILs were synthesized and characterized using NMR, FT-IR, TGA, and CHNS microanalysis and were used as the catalyst for raw biomass conversion. The remarkably high yield (i.e. 88%) of C5 sugars from bagasse can be obtained using 1-methyl-3(3-sulfopropyl)-imidazolium hydrogen sulfate ([C3SO3HMIM][HSO4]) BAIL catalyst in a water medium. Similarly, the [C3SO3HMIM][HSO4] BAIL also converts the bagasse into furfural with very high yield (73%) in one-pot method using a water/toluene biphasic solvent system.

Depolymerization of lignin using a solid base catalyst - Chaudhary, Richa; Dhepe, Paresh L. (Energy & Fuels, 2019)
Lignin extraction from lignocellulosic biomass has attracted considerable attention for an alternative production of sustainable fuels and chemicals. We report the lignin isolation from coconut coir using Klason, organosolv, and soda methods and the depolymerization of isolated lignin to value-added chemicals using a solid base catalyst. The yield of isolated lignin by the Klason method was found to be about 4 to 6 times higher than that by other methods. The structure of isolated Klason lignin (CC-KL), organosolv lignin (CC-ORGL), and soda lignin (CC-SL) was studied using attenuated total reflection (ATR), NMR, microanalysis, and so forth. The monomer molecular formula derived from microanalysis suggested that coir lignin is rich in guaiacyl units. ATR and C-13 NMR clearly indicate that CC-ORGL contains more C-C bonds compared to CC-KL and CC-SL. Subsequently, these isolated lignins were depolymerized over a solid base catalyst (NaX) under atmospheric pressure. CC-SL shows a high yield of aromatic products (28%) compared to CC-ORGL and CC-KL. In order to develop a sustainable future technology, one-pot depolymerization of coconut coir was performed which resulted in a high yield (64%) of aromatic products.

Designing an industrially viable bimetallic catalyst for the polyol synthesis - Kadam, Jyoti R.; Khan, Tufeil Sartaj; Dhepe, Paresh L. (New Journal of Chemistry, 2023)
Designing new catalysts for the hydrogenation of sugars is important since the conventional catalyst RANEY (R) Ni faces issues such as leaching, operation under severe conditions (similar to 100 bar H-2) to achieve better yields and formation of complexes of Ni with polyols. To overcome these issues and to have an industrially acceptable methodology, bimetallic catalysts with varying metal loadings (Ru = 1.5 and 2 wt% and Co = 1.5, 3, and 4 wt%) were synthesized in the current work and their hydrogenation activities were evaluated for the synthesis of sugar alcohols from various sugars. It was revealed that the nature of the support plays an important role in deciding the selectivity and activity of the catalyst and amongst all the supports, basic alumina showed the best activity due to its contribution to the ring opening of sugars. C5 and C6 sugars were successfully hydrogenated to their respective sugar alcohols under low H-2 pressures (15 bar) and it was observed that as compared to the monometallic (1.5)Ru/Al-Basic catalyst, the bimetallic (1.5)Ru(3)Co/Al-Basic catalyst showed enhancement in the activity by almost 1.5 times. The improvement in the activity is suggested to be due to (i) observance of the synergistic effect between the base metal (Ru) and the promoter metal (Co); (ii) effect of basicity of the support; and (iii) electronic effect of Ru and Co. Recyclability of the catalysts and their efficiency to hydrogenate higher concentration substrate solutions (10-20 wt%) make the overall process industrially attractive.